2018
DOI: 10.1093/mnrasl/sly026
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of phosphorus nitride in star-forming regions

Abstract: We present multi-transition observations of PN towards a sample of nine massive dense cores in different evolutionary stages. Using transitions with different excitation conditions, we have found for the first time that the excitation temperatures of PN are in the range ∼5-30 K. To investigate the main chemical route for the PN formation (surface-chemistry vs. gas-phase chemistry), and the dominant desorption mechanism (thermal vs. shock), we have compared our results with those obtained from molecules tracing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 35 publications
10
71
0
1
Order By: Relevance
“…As shown in Figure 1 for the long-lived collapse case (see bottom panels), these upper limits are consistent with the low gas-phase PN abundances predicted at a few 10 5 yr after the end of the collapse in cold high-density cores (with hydrogen gas densities 2×10 5 cm −3 ). For massive starless cores, which show slightly warmer temperatures (with T∼25-30 K; Fontani et al 2016), the derived abundances of PN are ∼10 −11 and 5×10 −12 (Mininni et al 2018), in agreement with those predicted by our models under warm temperatures for n(H)2×10 5 cm −3 and timescales of a few 10 5 yr (see models with T=50 K in Figure 2). No upper limits are available for PO toward low-mass/high-mass cold cores.…”
Section: Pn and Posupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure 1 for the long-lived collapse case (see bottom panels), these upper limits are consistent with the low gas-phase PN abundances predicted at a few 10 5 yr after the end of the collapse in cold high-density cores (with hydrogen gas densities 2×10 5 cm −3 ). For massive starless cores, which show slightly warmer temperatures (with T∼25-30 K; Fontani et al 2016), the derived abundances of PN are ∼10 −11 and 5×10 −12 (Mininni et al 2018), in agreement with those predicted by our models under warm temperatures for n(H)2×10 5 cm −3 and timescales of a few 10 5 yr (see models with T=50 K in Figure 2). No upper limits are available for PO toward low-mass/high-mass cold cores.…”
Section: Pn and Posupporting
confidence: 87%
“…In this section, we compare our modeling results to the abundances of PN and PO measured toward low-mass/ high-mass starless/pre-stellar cores (Turner et al 1990;Mininni et al 2018), massive hot cores (Turner et al 1990;Rivilla et al 2016), GMCs in the Galactic center (Rivilla et al 2018), and molecular outflows (Yamaguchi et al 2011;Lefloch et al 2016). …”
Section: Pn and Pomentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works Mininni et al 2018) suggested a correlation between the presence of shocks and/or high velocity material traced by SiO, and the detection of PN. However, this tentative conclusion was based on a limited number of sources, and the samples were predominantly biased towards sources dominated by shocks.…”
Section: Source Samplementioning
confidence: 94%
“…Small P-bearing molecules including PO, PN, CP, and HCP have been detected towards evolved stars (Agúndez et al 2007;Tenenbaum et al 2007;Ziurys et al 2007;Milam et al 2008), but attempts to detect these molecules towards active star-forming regions have had mixed results. In massive star forming regions, PN has been found fairly commonly (Turner & Bally 1987;Fontani et al 2016;Mininni et al 2018), while PO has been detected towards only two high-mass star forming regions despite numerous searches (Matthews et al 1987;Fontani et al 2016;Rivilla et al 2016). In low-mass star forming regions, PN and PO were detected in the outflow shock of the protostar L1157, but not towards the protostellar envelope (Yamaguchi et al 2011;Lefloch et al 2016).…”
Section: Introductionmentioning
confidence: 99%